ABSORBER PLATES POSITION INFLUENCE ON SOLAR COLLECTOR OPERATION EFFICIENCY - M. M. Asanov (Известия высших учебных заведений: Проблемы энергетики)
In order to increase the operating efficiency of solar power generating system its absorbing surface must be continuously turned towards the Sun. Modern Sun tracking systems are analyzed. Operation of solar air wall-type collector is considered. Collector’s absorber plates were situated in two ways – horizontally and vertically. Operation of the collector with horizontally situated plates is to turn of the plates towards the Sun according to solar altitude angle. Vertically situated plates position depends on solar azimuth angle. Cross shading of the absorbers plates during Sun tracking is calculated. To estimate the collector efficiency its operation within two days of the year (1.01.2016 and 11.06.2016) is studied. In order to compare the collectors’ characteristics with different types of the absorber the mathematical model is built.